N-terminal strategy (N1–N4) toward high performance liquid crystal materials. Issue 10 (10th March 2016) - Hong, Fengying; Xia, Zhengce; Zhu, Dezhao; Wu, Hongxiang; Liu, Jianhui; Zeng, Zhuo
Abstract: Liquid crystal materials have a variety of applications in many fields such as display techniques as well as photonics and optics. However, only few design principles have been disclosed on liquid crystal materials with different N-heterocycles as the terminal groups, which hinder the development of the heterocyclic liquid crystals. Here, a strategy of molecular design for N-heterocyclic liquid crystal materials is reported. On the basis of this strategy, a series of convenient N-heterocycles such as pyrrole, pyrazole, imidazole, 1, 2, 3-triazole, 1, 2, 4-triazole, 1, 2, 3, 4-tetrazole were applied to synthesize the novel liquid crystals. Most of them have proved to exhibit good mesomorphic behaviors which make them excellent components in the mixture of the LCDs materials. The simple attachment of N-heterocyclic units to the liquid crystal molecules through a mild reaction condition will provide a good prospect for the design of N-heterocyclic liquid crystals. Graphical abstract: A series of N-heterocyclic liquid crystal materials were synthesized. The properties of new compounds can be adjusted by varying the bridge and/or the terminal N-heterocycles. The compounds with difluoromethylene linker displayed excellent physical and electro-optical characteristics which offer a new approach for the development of high performance liquid crystal materials.